2023
DOI: 10.3390/foods12040760
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Antioxidant Properties of Essential Oils of M. pulegium (L.), M. suaveolens (Ehrh.) and M. spicata (L.) from Moroccan Middle-Atlas

Abstract: The cosmetics and food fields are based on the use of synthetic substances to protect their products against oxidation. However, synthetic antioxidants were reported to have negative effects on human health. The interest to develop natural antioxidants from plants has been growing in recent decades. The aim of this study was to determine the antioxidant properties of three essential oils (EOs) of M. pulegium (L.), M. suaveolens (Ehrh.) and M. spicata (L.) from the Azrou and Ifrane regions. The organoleptic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
0
0
Order By: Relevance
“…The yield of EO for S. officinalis obtained in our study was higher than the one reported by Jack et al (2%) [27]. Regarding T. zygis, a greater yield has been obtained compared to that obtained by Zekri et al (2017) (0.3%) [28]. The difference observed in the EO yield between the literature results and our study could be explained by an adaptation of the plant to abiotic factors, such as the climate specific to the sample's origin regions, to geographical factors, such as altitude, and the nature of the soil that directly interferes with the biosynthesis towards the preferential formation of specific products [29].…”
Section: Yields Of Eos Plantscontrasting
confidence: 77%
“…The yield of EO for S. officinalis obtained in our study was higher than the one reported by Jack et al (2%) [27]. Regarding T. zygis, a greater yield has been obtained compared to that obtained by Zekri et al (2017) (0.3%) [28]. The difference observed in the EO yield between the literature results and our study could be explained by an adaptation of the plant to abiotic factors, such as the climate specific to the sample's origin regions, to geographical factors, such as altitude, and the nature of the soil that directly interferes with the biosynthesis towards the preferential formation of specific products [29].…”
Section: Yields Of Eos Plantscontrasting
confidence: 77%
“…These results are in line with previous studies, which also identified pulegone as the main component of M. pulegium essential oil ( [38-40]. In addition, the presence of limonene and menthone in significant proportions [41,42].…”
Section: Chemical Analysissupporting
confidence: 93%
“…The physicochemical analysis of the essential oils of M. alternifolia and C. flexuosus was performed according to the protocol described by Zekri et al (2023) [44]. The solubility properties of the essential oils were determined using varying concentration of Tween-80.…”
Section: Physicochemical Analysis Of Essential Oilmentioning
confidence: 99%
“…This was performed using the broth microdilution checkerboard method as described by Satyajit et al (2007) [44] with slight modification. A 96-well microtiter plate was used for this experiment.…”
Section: Determination Of Synergism Of the Combination Of The Essenti...mentioning
confidence: 99%